The relevance of process emissions for carbon leakage: A comparison of unilateral climate policy options with and without border carbon adjustment - Bednar-Friedl, Birgit; Schinko, Thomas; Steininger, Karl W. (Energy economics, 2012)
Climate policy arrangements of partial regional coverage, as they seem to emerge from the UNFCCC process, might lead to carbon leakage and hence a broad literature has developed to quantify leakage. Most of these analyses, however, are confined to consider emissions from fuel combustion only. Yet, some of the most relevant simultaneously energy intensive and internationally trade exposed sectors are also subject to substantial emissions from industrial processes. Carbon dioxide emissions can be released in industrial processes which physically or chemically transform materials. In the steel and cement sectors, for example, these process emissions amount to about half of sector carbon dioxide emissions in many countries. We incorporate industrial process emissions based on UNFCCC data into a multi-sectoral multi-regional computable general equilibrium model and analyze the implications of a unilateral EU 20% carbon dioxide emission reduction policy on leakage and the effectiveness of border carbon adjustment in reducing leakage. By comparing the results to a model without process emissions, we find that leakage of climate policy so far has been underestimated. Leakage turns out to be higher when process emissions are correctly accounted for (38% instead of 29% for combustion emissions only). Conversely, border carbon adjustment measures are found to be roughly twice as effective to reduce leakage rates, when process emissions are correctly accounted for — as carbon adjustment rates are more directly targeted to the relevant sectors. Yet, border carbon adjustment measures should not be seen as a panacea as they might impede necessary technological carbon-free innovation, unless they are phased out over time. ► Industrial process emissions (IPE) acknowledgement significantly raises leakage. ► Border carbon adjustment (BCA) measures covering IPE as well are more effective. ► Reason 1: IPE intensive sectors are particularly trade exposed. ► Reason 2: IPE intensive sectors have higher emission intensity in non-EU regions. ► These results do not hold for other non-combustion emissions also neglected in analyses yet.